Tuberculosis Control Program Management in the Donggala Community Health Center Work Area - Sudirman; Indra Afrianto; Titin Setiyawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Low public awareness in TB treatment, at least 6 months and many cases of drug discontinuation which causes resistance to anti-tuberculosis drugs also affect transmission, do not understand how to treat. The purpose of this study was to determine the analysis of tuberculosis patient management in the Donggala District Health Center area. This research method uses a qualitative method to explain and describe (in words) the implementation of TB case finding at the Donggala Health Center so that the research results can be conveyed in depth, with 7 informants. Based on the research results, the community in the Donggala Health Center area has a diverse understanding, some people are aware of the dangers of TB and the importance of regular treatment. Health workers have an important role in finding new cases of TB. They carry out active screening by going directly to the community, conducting close contact investigations, and working with health cadres and the village government. The conclusion is that health services in the Donggala Health Center area are quite available, with the presence of laboratories and medical personnel who can carry out TB examinations and diagnoses quickly. Research suggestions can expand the reach of education to the community about the importance of TB prevention, compliance with taking medication, and the risk of spreading the disease.